Assessing negative symptoms in schizophrenia : validity of the clinical assessment interview for negative symptoms in Singapore - Rekhi, Gurpreet (2021)
This study aimed to examine the validity of the Clinical Assessment Interview for Negative Symptoms (CAINS) in Singapore. 274 participants with schizophrenia were assessed on the CAINS, Scale for the Assessment of Negative Symptoms (SANS), Positive and Negative Syndrome Scale (PANSS), Calgary Depression Scale for Schizophrenia (CDSS), Social and Occupational Functioning Assessment Scale (SOFAS) and the Simpson-Angus Extrapyramidal Side Effects Scale (SES). Factor analyses were conducted and Cronbach's coefficient alpha was calculated. Spearman's correlation coefficient was used to assess correlations. The 2-factor model of the CAINS failed to fit our data. Exploratory factor analysis of a randomly selected split-half of the sample yielded four factors: motivation-pleasure (MAP) social, MAP vocational, MAP recreational and expression (EXP), accounting for 73.94% of the total variance. Confirmatory factor analysis on the remaining sample supported this factor structure. Cronbach's alpha for the CAINS was 0.770. Significant correlations were observed between the CAINS total and the SANS total and PANSS negative subscale scores. Good divergent validity was shown by insignificant correlations with PANSS positive subscale score and CDSS total score. The MAP social and recreational factor scores had moderate correlations with the SANS anhedonia-asociality subscale scores, whereas the MAP vocational factor had the highest correlation with the avolition-apathy subscale of the SANS. EXP factor score correlated strongly with the SANS affective flattening and alogia subscales scores. In conclusion, the CAINS has good psychometric properties and can be used by clinicians to assess negative symptoms in individuals with schizophrenia in the local population.